Understanding Basic Accounting Concepts Using a Service Company Example (Študije primerov EPF: Razvoj, trajnost in inovacije v poslovni praksi 2024, 2024)
With our case study, we want to present the reader with the practical example of the establishment of a microservice firm and further business events that occur in its first month of operation, the approach to analysing these business events, and the assessment of how they affect the financial situation and performance of the firm. The study avoids delving into extensive accounting rules or bookkeeping techniques. Still, it is crucial to understand the accrual basis of accounting and the interrelated changes of economic categories, which are pursued in the case study by consistently following the accounting equation and accounts' balance. The latter is a key rule that is realised in all subsequent activities within accounting, such as bookkeeping and preparing a firm's financial statements. The case study is suitable for anyone who wants to understand the basic concepts of how accounting works and how it thinks, regardless of their professional background. Such knowledge is helpful in making a variety of business, management, and even household decisions, as it provides insight into the complex treatment of any business event or decision and, above all, its/their consequences on the performance and financial position (of a firm or an individual).